A Novel Liquid–Liquid Extraction for the Determination of Nicotine in Tap Water, Wastewater, and Saliva at Trace Levels by GC-MS. (27th November 2019) - Dobrowska, Joanna Sonia; Erarpat, Sezin; Chormey, Dotse Selali; Pyrzyńska, Krystyna; Bakirdere, Sezgin
Abstract: Determination of nicotine at trace levels in different matrixes is crucial because of nicotine's strongly addictive property. In this study, a simple and fast analytical method was developed using liquid–liquid extraction with GC-MS. Chloroform was used as an extraction solvent. Different parameters for extraction, such as pH of the solution, types and volumes of extraction and supporter solvents for dispersion, extraction period, and salt type and its amount, were optimized. To improve the precision, naphthalene was used as an internal standard. The calibration plot of nicotine was linear from 0.010 to 2.0 mg/L with a correlation coefficient 0.9996. The LOD and LOQ for nicotine after extraction were 2.6 and 8.8 ng/mL, respectively. Under the optimum conditions, tap water, wastewater, and saliva samples were analyzed for their nicotine content. The spiking experiments yielded satisfactory recoveries of 97.6 ± 3.5, 96.8 ± 1.1, and 85.1 ± 1.3% for tap water, wastewater, and saliva samples, respectively.